Intragenerational Cultural Evolution and Ethnocentrism. (May 2019) - Hales, David; Edmonds, Bruce
Ethnocentrism denotes a positive orientation toward those sharing the same ethnicity and a negative one toward others. Previous models demonstrated how ethnocentrism might evolve intergenerationally (vertically) when ethnicity and behavior are inherited. We model short-term intragenerational (horizontal) cultural adaptation where agents have a fixed ethnicity but have the ability to form and join fluid cultural groups and to change how they define their in-group based on both ethnic and cultural markers. We find that fluid cultural markers become the dominant way that agents identify their in-group supporting positive interaction between ethnicities. However, in some circumstances, discrimination evolves in terms of a combination of cultural and ethnic markers producing bouts of ethnocentrism. This suggests the hypothesis that in human societies, even in the absence of direct selection on ethnic marker–based discrimination, selection on the use of fluid cultural markers can lead to marked changes in ethnocentrism within a generation.